Produtividade e valor nutricional de variedades de cana-de-açúcar sob diferentes fontes de fósforo - Caione, Gustavo [UNESP]; Fernandes, Francisco Maximino [UNESP]; Lange, Anderson; Bergamaschine, Antonio Fernando [UNESP]; Dalchiavon, Flávio Carlos; Silva, Amilton Ferreira da (Universidade Estadual de Londrina (UEL), 2012)
Due to the expansion of sugarcane in areas that are not traditional in it's cultivation, there is need of study the management of fertilizer, mainly phosphorus, since it's the nutrient that most limits the production in the tropics. The aim of this work was to evaluate the productivity and nutritional value of two varieties of sugarcane grown under different phosphorus sources, for three production cycles in North of Mato Grosso State, Brazil. The experimental design was randomized blocks in factorial scheme 4x2, with four replications. The sources of phosphorus used were bone meal, Arad phosphate and triple superphosphate at a dose of 100 kg P2O5 ha(-1), and a control without nutrient application at planting. The varieties of sugarcane were planted IAC86-2480 and SP79-1011. We evaluated the productivity of dry matter, dry matter content, neutral detergent fiber and acid detergent, lignin, cellulose, in vitro digestibility and crude protein of forage. The phosphorus sources provided higher yields during the first cycle of sugarcane and did not cause significant effect on productivity in subsequent cycles. Phosphorus fertilization did not cause significant changes in the nutritional value of sugarcane. The variety IAC86-2480 showed higher crude protein content in three cycles and higher dry matter yield in the first two cycles, compared to SP79-1011. Regarding the fiber constituents, both showed similar results.
Productivity and nutritional value varieties of sugarcane under different phosphorus sources
Keywords: Saccharum spp.; forage; phosphate fertilization; chemical composition; bone meal